2001
DOI: 10.1002/cyto.1068
|View full text |Cite
|
Sign up to set email alerts
|

DNA copy number amplifications in sarcomas with homogeneously staining regions and double minutes

Abstract: To identify DNA amplifications in sarcomas, comparative genomic hybridization was performed on 27 cases that were likely to display high-level DNA copy number gains. In all cases, chromosome banding analysis had revealed homogeneously staining regions or double minutes, i.e., cytogenetic signs of gene amplification. In most cases, gains predominated over losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In the literature, we found cytogenetic data corresponding to 161 cases of WDLPS and 44 UDLPS (Sreekantaiah et al,1992; Szymanska et al,1995; Fletcher et al,1996; Palmer et al,1997; Iwasaki et al,1998; Pilotti et al,1998; Dei Tos et al,2000; Menghi‐Sartorio et al,2001; Coindre et al,2004; Gisselsson et al,2004; Sandberg,2004; Bassett et al,2005; Heidenblad et al,2006; Benchetritt et al,2007; Macarenco et al,2007; Italiano et al,2008). Among the 161 WDLPS, 146 were associated with ring chromosomes (91%), and only 15 with marker chromosomes (9%).…”
Section: Resultsmentioning
confidence: 98%
“…In the literature, we found cytogenetic data corresponding to 161 cases of WDLPS and 44 UDLPS (Sreekantaiah et al,1992; Szymanska et al,1995; Fletcher et al,1996; Palmer et al,1997; Iwasaki et al,1998; Pilotti et al,1998; Dei Tos et al,2000; Menghi‐Sartorio et al,2001; Coindre et al,2004; Gisselsson et al,2004; Sandberg,2004; Bassett et al,2005; Heidenblad et al,2006; Benchetritt et al,2007; Macarenco et al,2007; Italiano et al,2008). Among the 161 WDLPS, 146 were associated with ring chromosomes (91%), and only 15 with marker chromosomes (9%).…”
Section: Resultsmentioning
confidence: 98%
“…A case report of a large cell medulloblastoma patient by Reardon et al identified amplification of both 2p24 and 2q12-22 as well, suggesting an association between the 2q14-21 interval and N-myc amplification (31). While amplifications at 2q14-21 are not common in neoplasms, they have been reported in several sarcomas (23). The oncogene(s) involved in this region remain to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of oncogenes through amplification at the chromosome level plays an important role in the development of many malignant tumor types. Cytogenetically, gene amplification can be observed in three principally and mechanistically different forms: double minutes (dmin), homogeneously staining regions (hsr), and ring chromosomes/giant marker chromosomes (hereafter referred to as rings) (Cox et al, 1965; Kopnin, 1981; Barker, 1982; Cowell, 1982; Gebhart et al, 1984; Schwab, 1998; Gisselsson et al, 1999; Pedeutour et al, 1999; Menghi‐Sartorio et al, 2001; Storlazzi et al, 2006; Hattinger et al, 2009). Depending on tumor type, the genomic contents of the amplicons vary, with different target genes in different tumors.…”
Section: Discussionmentioning
confidence: 99%